Pathological and clinical features of multiple cancers and lung adenocarcinoma: a multicentre study. (21st February 2022) - Bertoglio, Pietro; Ventura, Luigi; Aprile, Vittorio; Cattoni, Maria Angela; Nachira, Dania; Lococo, Filippo; Rodriguez Perez, Maria; Guerrera, Francesco; Minervini, Fabrizio; Gnetti, Letizia; Lenzini, Alessandra; Franzi, Francesca; et al.
Abstract: OBJECTIVES: Lung cancer is increasingly diagnosed as a second cancer. Our goal was to analyse the characteristics and outcomes of early-stage resected lung adenocarcinomas in patients with previous cancers (PC) and correlations with adenocarcinoma subtypes. METHODS: We retrospectively reviewed data of patients radically operated on for stage I–II lung adenocarcinoma in 9 thoracic surgery departments between 2014 and 2017. Overall survival (OS) and time to disease relapse were evaluated between subgroups. RESULTS: We included 700 consecutive patients. PC were present in 260 (37.1%). Breast adenocarcinoma, lung cancer and prostate cancer were the most frequent (21.5%, 11.5% and 11.2%, respectively). No significant differences in OS were observed between the PC and non-PC groups ( P = 0.378), with 31 and 75 deaths, respectively. Patients with PC had smaller tumours and were more likely to receive sublobar resection and to be operated on with a minimally invasive approach. Previous gastric cancer ( P = 0.042) and synchronous PC (when diagnosed up to 6 months before lung adenocarcinoma; P = 0.044) were related, with a worse OS. Colon and breast adenocarcinomas and melanomas were significantly related to a lower incidence of high grade (solid or micropapillary, P = 0.0039, P = 0.005 and P = 0.028 respectively), whereas patients affected by a previous lymphoma had a higher incidence of a micropapillary pattern ( P = 0.008). CONCLUSIONS: In patients with PC, we found smaller tumours more frequently treated with minimally invasive techniques and sublobar resection, probably due to a more careful follow-up. The impact on survival is not uniform and predictable; however, breast and colon cancers and melanoma showed a lower incidence of solid or micropapillary patterns whereas patients with lymphomas had a higher incidence of a micropapillary pattern. Abstract : Lung cancer is the leading cause of death of cancer worldwide, and adenocarcinoma is the most frequent histotype [1].